., Conservation Program Through Ex-Situ Cptive Breeding Of Primates at IPB Research Center - Iskandar, Entang (Prosiding KPSDA, 2015)
., Conservation Program Through Ex-Situ Cptive Breeding Of Primates at IPB Research Center